Will your next computer be a tin can and a wire? (Economist, 1995)
Considers claims that the Internet could destroy the personal computer (PC) industry. How PCs are caught in a vicious circle; Internet connections; Launch of Sun Microsystems' Java, a new programming language; Sun's goals; Argument that though specialized network computer may catch on, they will not kill the PC.